Molecular mapping of vernalization requirement and fertility restoration genes in carrot - Alessandro, Maria Soledad (2013)
Carrot (Daucus carota L.) is a cool-season vegetable normally classified as a biennial species, requiring vernalization to induce flowering. Nevertheless, some cultivars adapted to warmer climates require less vernalization and can be classified as annual. Most modern carrot cultivars are hybrids which rely upon cytoplasmic male-sterility for commercial production. One major gene controlling floral initiation and several genes restoring male fertility have been reported but none have been mapped. The objective of the present work was to develop the first linkage map of carrot locating the genomic regions that control vernalization response and fertility restoration. Using an F2 progeny, derived from the intercross between the annual cultivar ‘Criolla INTA’ and a petaloid male sterile biennial carrot evaluated over 2 years, both early flowering habit, which we name Vrn1, and restoration of petaloid cytoplasmic male sterility, which we name Rf1, were found to be dominant traits conditioned by single genes. On a map of 355 markers covering all 9 chromosomes with a total map length of 669 cM and an average marker-to-marker distance of 1.88 cM, Vrn1 mapped to chromosome 2 with flanking markers at 0.70 and 0.46 cM, and Rf1 mapped to chromosome 9 with flanking markers at 4.38 and 1.12 cM. These are the first two reproductive traits mapped in the carrot genome, and their map location and flanking markers provide valuable tools for studying traits important for carrot domestication and reproductive biology, as well as facilitating carrot breeding.